Method for Producing Glycolic Acid
The continuous flow process using a ruthenium-tin catalyst in a fixed bed reactor effectively converts oxalic acid to glycolic acid with high selectivity and conversion rates at lower temperatures and shorter times, addressing the inefficiencies of existing batch processes.
Patent Information
- Application Number
- JP2024555189
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-15
- Filing Date
- 2023-03-14
- Publication Date
- 2025-04-11
AI Technical Summary
Current methods for converting oxalic acid to glycolic acid face challenges such as low selectivity and high energy requirements, particularly due to the need for high temperatures which can lead to decomposition of oxalic acid and the formation of by-products.
A continuous flow process in a fixed bed reactor using a supported metal-containing hydrogenation catalyst, specifically a ruthenium-tin catalyst, to hydrogenate an aqueous oxalic acid solution at temperatures between 40°C and 85°C, achieving high conversion and selectivity of oxalic acid to glycolic acid.
This method achieves high selectivity (80% or more) of glycolic acid production from oxalic acid with conversion rates of 80% to 100%, while operating at significantly lower temperatures and shorter residence times compared to existing batch processes, making it industrially viable.
Smart Images

Figure 2025509771000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a process for producing glycolic acid, comprising the hydrogenation of oxalic acid. [Background technology]
[0002] In view of the climate change issue, many efforts are being developed to reduce the amount of greenhouse gases in the atmosphere. The emphasis on CO2 capture continues to increase, with CO2 being mostly captured from large point production, such as chemical or power plants, industries with significant CO2 emissions (e.g. steelmaking), natural gas processing, production of hydrogen from fossil fuels, etc. After capture, the next step is the storage (CCS) and / or utilization (CCU) of CO2. The big difference between storage and utilization is that CCS technologies store CO2 underground so that it cannot re-enter the atmosphere, while CCU technologies use CO2 to convert it into more valuable products, such as plastics or biofuels. Especially nowadays, traditional fossil sources of energy generation can be replaced (at least in theory) with net-zero emission methods, but this is not the case for producing materials such as plastics or concrete. Therefore, the use of CO2 to produce materials is important to ensure a low impact on natural resources and is one of the few options to achieve negative emissions (provided at least that non-fossil CO2 and renewable energy are used).
[0003] For example, CO2 can be used to produce oxalic acid (HOOCCOOH), which can then be hydrogenated to produce, for example, glycolic acid (HOCH2COOH; GA) and monoethylene glycol (HOCH2CH2OH; MEG), which are valuable chemicals for many different applications, such as for the production of plastics and for GA as a preservative in food processing, a skin care agent in cosmetics, etc.
[0004] However, the hydrogenation of carboxylic acids, an important organic reaction for the synthesis of useful and valuable chemicals, is a chemically challenging reaction due to the low reactivity and acidity of the carboxyl group. The reaction requires, for example, the rational design of catalysts. See Tamura, M. et al., Recent Developments of Heterogeneous Catalysts for Hydrogenation of Carboxylic Acids to Their Corresponding Alcohols. Asian J. Org. Chem. 2020, 9(2), 126-143.
[0005] Thus, direct reduction of carboxylic acids requires harsh conditions. However, high temperatures cannot be used because oxalic acid begins to decompose above 130° C. to produce CO2 and formates, and also methane under hydrogenation conditions. As a result, there are few disclosures in the art about this particular reaction.
[0006] Catalytic hydrogenation of oxalic acid over a ruthenium-carbon catalyst has been reported by Santos et al. (Reaction Kinetics, Mechanism and Catalysis (2020) 131:139-151). They investigated the reduction of oxalic acid in a slurry reactor in the presence of a 5 wt.% Ru / C microporous catalyst at a pressure of 80 bar and a temperature range of 120-150 °C under continuous gas flow in a batch mode with a run time of 7 h. They observed the formation of glycolic acid, acetic acid, ethylene glycol, and volatile compounds. The conversion of oxalic acid reached over 90%, with the highest run selectivities being 63% (120 °C) for glycolic acid, 16% (130 °C) for ethylene glycol, and 87% (150 °C) for volatile products, respectively.
[0007] WO2017134139 discloses a method for preparing glycolic acid and / or ethylene glycol, comprising at least the steps of: (a) obtaining an oxalic acid-containing aqueous stream having a molar ratio of water / oxalic acid greater than 5.0; (b) subjecting the oxalic acid-containing aqueous stream obtained in step (a) to hydrogenation in the presence of a metal hydride catalyst and hydrogen, thereby obtaining a glycolic acid-containing stream; and (c) optionally subjecting the glycolic acid-containing stream obtained in step (b) to hydrogenation in the presence of a metal hydride catalyst and hydrogen, thereby obtaining an ethylene glycol (HOCH2CH2OH)-containing stream. All of the examples in WO2017134139 operate in a batch mode. The highest selectivity of glycolic acid reported in the batch process of WO2017134139 is 76% at a conversion of oxalic acid of 80%, produced after a reaction time of 4 hours at 100°C and H2 pressure of 100-120 bar.
[0008] From the Santos publication and WO2017134139, respectively, it can be seen that at a relatively high temperature (120°C) and a run time of 7 hours, the conversion of oxalic acid is relatively high (91%) but this comes at the expense of selectivity to glycolic acid (only 63%), whereas at a lower temperature (100°C) and a reaction time of 4 hours, the selectivity to glycolic acid is higher (76%) but the conversion of oxalic acid is reduced (80%). [Prior art documents] [Patent documents]
[0009] [Patent Document 1] WO2017134139 [Non-patent literature]
[0010] [Non-Patent Document 1] Tamura, M. et al., Recent Developments of Heterogeneous Catalysts for Hydrogenation of Carboxylic Acids to Their Corresponding Alcohols. Asian J. Org. Chem. 2020, 9(2), pp. 126-143 [Non-Patent Document 2] Santos et al. (Reaction Kinetics, Mechanism and Catalysis (2020) 131:139-151) [Non-Patent Document 3] Oxalic acid Wikipedia page: References A. Apelblat et al. (1987), The Journal of Chemical Thermodynamics, Volume 19, Issue 3, Pages 317-320 [Non-Patent Document 4] S. Taniguchi et al. / Applied Catalysis A: General 397 (2011) pp. 171-173 Summary of the Invention [Problem to be solved by the invention]
[0011] There remains a need for a process for converting oxalic acid to glycolic acid that is characterized by both high conversion of the oxalic acid starting material and high yield of the desired glycolic acid product. In particular, the systems used in the Santos process, which have residence times of 4-7 hours, are not practical. It would be particularly advantageous to provide an industrially applicable continuous process for hydrogenating oxalic acid to selectively produce glycolic acid. [Means for solving the problem]
[0012] Accordingly, the present invention provides a method for producing glycolic acid, comprising the steps of subjecting an aqueous solution of oxalic acid to a hydrogenation reaction in the presence of hydrogen and a metal-containing hydrogenation catalyst, It is a continuous flow process in a fixed bed; Aqueous oxalic acid solutions contain no potassium; an aqueous oxalic acid stream and a hydrogen gas stream are fed to a fixed bed reactor, the aqueous oxalic acid stream in the feed stream having an oxalic acid concentration of up to 100% saturation at a feed temperature; the reactor comprises a hydrogenation catalyst bed, the catalyst being a supported metal-containing hydrogenation catalyst with a total metal loading of from 2.0 wt.% or more to 20.0 wt.% or less; The hydrogenation reaction is carried out at a temperature selected from the range of 40° C. or more and 85° C. or less, at a hydrogen pressure selected from the range of 10 bar H2 or more and 150 bar H2 or less, with a residence time of 5 minutes to 1 hour or less, providing a process in which glycolic acid is produced with a high selectivity of 80% or more at a conversion of 80% to 100% of oxalic acid.
[0013] Contrary to expectations, in this present continuous flow process, high conversion of oxalic acid and high selectivity for glycolic acid were found at significantly lower reaction temperatures and shorter reaction / residence times (commercially attractive time frames) than those of the prior art processes.
[0014] Advantageously, this novel process creates an opportunity for the efficient industrial production of glycolic acid from oxalic acid.
[0015] Detailed Description of the Invention The present invention relates to a continuous flow process for producing glycolic acid from oxalic acid. Continuous flow means that the process can be run without interruption and does not require frequent input of raw materials, in contrast to batch processes. Until now, only a few prior art publications have been related to the production of glycolic acid from oxalic acid, and such publications only describe the process in batch mode. A "batch process" refers to a process that has a beginning and an end, including a sequence of steps that follow in a specific order. The present continuous flow process refers to a process that is defined by the flow of reactants and products (step by step), and the process is run for a longer period of time, while new reactants are continuously fed and products are continuously removed. Batch processing usually requires more energy costs, more capital, and takes longer, but is often the safest and most manageable way to process a compound. Continuous processing is efficient and cost-effective, but is not necessarily suitable for every chemical reaction.
[0016] The presently disclosed continuous flow process is carried out in a fixed bed reactor (also called a packed bed reactor), which can be any fixed bed reactor known in the art, including, for example, a single cylindrical tube suitably filled / packed with a suitable catalyst, as well as a multi-tube reactor. The catalyst bed, often in the form of pellets, is placed in such a manner that it does not move relative to the reactor itself. The reactants, including reactant gases, flow uniformly over the fixed catalyst bed. A preferred type of fixed bed reactor for carrying out the present method is a trickle bed reactor. Trickle bed reactors include a family of reactors in which gas phase reactants flow in a downstream direction (towards the direction of gravity) over a bed of solid catalyst particles while reacting with a liquid phase reactant. The gas phase flow can be both upstream or downstream depending on the type of application. Preferably, in the present method, the gas phase reactant (hydrogen gas) flows in a downstream direction along with the liquid phase reactant (aqueous oxalic acid solution).
[0017] According to the method, an aqueous potassium-free oxalic acid solution and a hydrogen gas stream are fed to a fixed bed reactor, and the aqueous oxalic acid solution in the feed stream has a concentration of up to 100% saturation at the feed temperature. The term "saturation" as used herein relates to the solubility of oxalic acid in an aqueous solution, i.e., it defines the degree to which oxalic acid dissolves at a given temperature compared to the maximum possible temperature. A 100% saturated aqueous oxalic acid solution means an aqueous oxalic acid solution at that temperature in which the maximum amount of oxalic acid is dissolved. Examples of 100% saturated aqueous solutions of oxalic acid at various temperatures: 46.9 g / L (5 °C), 57.2 g / L (10 °C), 75.5 g / L (15 °C), 95.5 g / L (20 °C), 118 g / L (25 °C), 139 g / L (30 °C), 178 g / L (35 °C), 217 g / L (40 °C), 261 g / L (45 °C), 315 g / L (50 °C), 376 g / L (55 °C), 426 g / L (60 °C), 548 g / L (65 °C) (Wikipedia page on oxalic acid: see references A. Apelblat et al. (1987), The Journal of Chemical Thermodynamics, Vol. 19, No. 3, pp. 317-320). Suitably, a highly concentrated aqueous solution of oxalic acid is used, preferably at least 80%, but more preferably as concentrated as possible at the feed temperature, ie most preferably 100% saturated.
[0018] In terms of mass percentage, preferably the aqueous oxalic acid solution contains 1.0% to 40% by mass oxalic acid, preferably 2.5% or more, more preferably 5.0% to 20% by mass oxalic acid.
[0019] The selected temperature of the aqueous oxalic acid solution in the feed stream (the "feed temperature") is generally the same temperature at which the hydrogenation reaction is carried out.
[0020] To increase the solubility of oxalic acid in water, certain additives, such as alcohols, ethers, etc., which are inert under reaction conditions, may be used in aqueous solutions of oxalic acid. The presence of such additives in an aqueous solution therefore has an effect on saturation, meaning that a solution that is, for example, 100% saturated, will contain more oxalic acid per liter than one without such additives.
[0021] Suitably, the aqueous oxalic acid solution used as the feed stream may be or may comprise a recycle stream from the hydrogenation reaction. Said recycle stream may thus comprise one or more hydrogenation (by)products, such as glycolic acid, ethylene glycol, glyoxylic acid, acetic acid, etc. Preferably, the aqueous oxalic acid solution used as the feed stream comprises a total of up to 20% by weight of such hydrogenation (by)products.
[0022] The aqueous oxalic acid solution used as the feed stream does not contain potassium in any form, the presence of which is considered toxic to the activity of the catalyst. The term "potassium-free" suitably means that the amount of potassium in the aqueous oxalic acid solution is less than 0.9 wt% (9000 ppm), preferably less than 0.5 wt%, especially less than 0.1 wt%.
[0023] Suitably, the catalyst in the fixed bed is a supported metal-containing hydrogenation catalyst with a total metal loading of from 2.0 wt% to 20.0 wt%, preferably from 3.0 wt% to 15.0 wt%, more particularly to 12.0 wt%.
[0024] The hydrogenation catalyst preferably contains one or more metals selected from the group A metals: platinum, nickel, copper, ruthenium, rhodium and iridium, and preferably ruthenium. In addition, the hydrogenation catalyst optionally also contains one other metal selected from the group B metals: tin, bismuth, palladium, rhenium, gold and antimony. Preferably, the hydrogenation catalyst contains ruthenium (group A metal), and preferably one group B metal.
[0025] Highly preferred hydrogenation catalysts contain ruthenium and tin. Such ruthenium-tin catalysts can be advantageously used to suppress the formation of by-products, such as over-reduction products such as acetic acid and ethylene glycol at high oxalic acid conversion. The molar ratio of ruthenium and tin in the catalyst is 10:1 to 1:10, preferably 5:1 to 1:5, more preferably 5:2 to 1:4.
[0026] Further preferred catalysts for use in the present process are trimetallic catalysts containing ruthenium, platinum and tin. See for example S. Taniguchi et al. / Applied Catalysis A: General 397 (2011) pp. 171-173. The amounts and molar ratios of ruthenium and tin in the trimetallic catalyst are selected as described above. The amount of platinum is preferably 1 to 5% by weight, more preferably 1.5 to 3% by weight, relative to the catalyst support. A highly preferred catalyst for optimal production of glycolic acid from oxalic acid is Ru1Sn 0.85 Pt 0.2 / C, the catalyst has a metal loading of 5 wt% ruthenium, 5 wt% tin and 2 wt% platinum. The rate of oxalic acid conversion increases when platinum is present in the catalyst.
[0027] Advantageously, chloride is absent from the catalyst used in the present process, which is considered important for catalyst stability.
[0028] Preferably, the catalyst used in the process according to the present disclosure is calcined (pretreated) prior to use at a temperature selected from 200°C to 450°C.
[0029] The catalyst support may be selected from any support material that does not inhibit the ongoing hydrogenation reaction. Preferably, the hydrogenation catalyst is supported on a support selected from carbon, silicon carbide, MAX-phase (Ti2Al2C), TiO2 and ZrO2, more preferably on carbon or MAX-phase, most preferably on carbon.
[0030] According to the present invention, reaction conditions have been found to be highly useful in a continuous flow process for selectively producing glycolic acid with high oxalic acid conversion at relatively low temperatures. Temperatures from 40° C. or higher, preferably 50° C. or higher, to 85° C. or lower, and advantageously, in particular at least 80% selectivity for glycolic acid are obtained with oxalic acid conversions of 80% or higher to 100%, including 100%, within a commercially attractive time frame. In one advantageous embodiment, the temperature is from 60° C. or higher to 85° C. or lower.
[0031] The commercially attractive time frame in which the present continuous flow process is carried out is expressed in terms of "residence time". The term "residence time" defines the average length of time that the feed stream, or specifically the molecules in the feed stream, remain inside the reactor, which herein means inside the part containing the catalyst bed. According to the present process, a residence time of at least 5 minutes and up to 2 hours is required. Preferably, the residence time is at least 10 minutes and up to 1 hour. In a flow reactor suitable for the present hydrogenation reaction, the residence time can vary depending on various factors such as the volume of the reactor, the feed flow rate (both the oxalic acid solution and hydrogen gas), the length of the catalyst bed, etc. In a batch process, compared to a continuous flow process, the residence time can be related to the reaction time, i.e., the length that the container is kept at a particular temperature in a batch process.
[0032] According to the general rule in chemistry defined by the Arrhenius equation, as a rule of thumb, the rate of a reaction roughly doubles (or halves, respectively) for every 10°C above (or below). Taking the prior art example of WO2017134139, considering a 76% selectivity of glycolic acid at 80% conversion of oxalic acid produced after 4 hours of reaction time at 100°C, these results suggest that carrying out the reaction at a lower temperature will certainly result in a lower conversion (for the same 4 hours of reaction time). Since carrying out the reaction 10°C below typically halves the reaction rate, the reaction by the prior art batch process of WO2017134139 carried out at 50°C is expected to have a reaction rate 2×2×2×2×2=32 times (5 times halved) slower than that at 100°C for the same reaction time. In other words, the reaction of WO2017134139 carried out at 50° C. has an estimated conversion of only 2-3% after 4 hours. As a result, to reach a result of 60 to 100% conversion at 50° C., the batch process of WO2017134139 would have to be run for at least 80 to 200 hours, which is clearly not commercially attractive.
[0033] In the process of the present invention, it has been found that increasing the feed flow does not affect the selectivity to glycolic acid. When the feed flow is very high, the residence time becomes very short and only the conversion of oxalic acid does not go to completion, but still selectively forms glycolic acid. Those skilled in the art will understand how to balance the feed flow at a certain temperature for the most appropriate residence time. At relatively high temperatures, shorter residence times (and therefore higher feed flows) are needed to maximize both the conversion of oxalic acid and the selectivity to glycolic acid. At high temperatures (specifically above about 95° C.), ethylene glycol may start to form by-products before the complete conversion of oxalic acid.
[0034] The process is carried out at a hydrogen pressure selected from the range of ≧10 bar H2 up to ≦150 bar H2, preferably from 20 to 100 bar H2.
[0035] The product stream of the continuous flow process according to the present disclosure may be continuously removed from the process and directly subjected to further processing if deemed necessary, however, the product stream may also be (partially) recycled before the desired glycolic acid is separated from the solution.
[0036] Oxalic acid is a corrosive substance. Stainless steel reactors are therefore not ideal for the present process. Therefore, advantageously, the present hydrogenation reaction is carried out in a reactor with a non-metallic or inert liner, such as Teflon, glass, PVC, titanium or Hastelloy.
[0037] A suitable and advantageous way of carrying out the method of the present invention comprises subjecting an aqueous potassium-free oxalic acid solution to a hydrogenation reaction in the presence of hydrogen and a metal-containing hydrogenation catalyst; the method is a continuous flow process in a trickle-flow Hastelloy reactor; 5-15% aqueous oxalic acid solution and a hydrogen gas stream are fed to the top of the reactor; the reactor is connected to a RuSn 0.85 Pt 0.2 % ruthenium, 4.7 wt % tin and 2 wt % platinum; the hydrogenation reaction is carried out at a temperature selected from the range of from 50° C. to 85° C., at a hydrogen pressure selected from the range of from 50 bar H2 to 100 bar H2, with a residence time of from 10 minutes to 45 minutes to produce glycolic acid with a high selectivity of 80% or more at a conversion of 90% to 100% of oxalic acid. [Brief description of the drawings]
[0038] [Figure 1] Results of QCS experiments with RuSn (5 wt.% / 5.9 wt) catalyst on different supports. Conversion (A), selectivity (B) and carbon balance (C) data were obtained by liquid chromatography (LC). Conditions during the reaction: temperature = 75 °C, pressure = 80 bar, substrate = oxalic acid (5 wt.%) in demineralized water (2 ml), catalyst / support loading = 50 mg, reaction time = 2, 4 and 6 h, respectively. [Diagram 2]Figure 1. Results of SFU experiments of oxalic acid reduction for different temperatures. Conversion (A), selectivity (B) and carbon balance (C) data were obtained by liquid chromatography (LC). Conditions during the reaction: temperature = 50-120 °C, pressure = 60 bar, feed stream = oxalic acid (5 wt.%) in water, feed flow = 0.1 ml min-1 (corresponding to a residence time of 18 min in the fully liquid state), gas (H2) flow = 200 ml min-1. In this reaction, Ru1Sn2.3 / C (calcined) was used as catalyst. [Diagram 3] Results of a 100-hour SFU experiment reducing oxalic acid produced by electrocatalytic CO2 reduction. Conversion (A), selectivity (B) and carbon balance (C) data were obtained by liquid chromatography (LC). Conditions during the reaction: temperature = 50 °C, pressure = 60 bar, feed stream = oxalic acid (2.37 wt.%) in water, feed flow = 0.1 ml min-1, gas (H2) flow = 200 ml min-1. Catalyst 9.76 wt.% Ru / C (0.5 wt.% water; Johnson Mattey). [Figure 4] Results of a 100-hour SFU experiment reducing commercial oxalic acid. Conversion (A), selectivity (B) and carbon balance (C) data were obtained by liquid chromatography (LC). Conditions during the reaction: temperature = 50 °C, pressure = 60 bar, feed = oxalic acid in water (2.37 wt.%), feed flow = 0.1 ml min-1, gas (H2) flow = 200 ml min-1. Catalyst 9.76 wt.% Ru / C (0.5 wt.% water; Johnson Mattey). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0039] The present invention is further illustrated by the following non-limiting examples.
[0040] List of abbreviations AA=Acetic acid EG = (mono)ethylene glycol GA = glycolic acid GlyA = glyoxylic acid MEG = (mono)ethylene glycol OA=Oxalic acid QCS=Quick Catalytic Screening SFU = Single Flow Unit
[0041] Experimental materials and reagents Oxalic acid (C2H2O4) was obtained from Sigma-Aldrich, dried and stored in a dry environment. All water used during this procedure was filtered using a Millipore system.
[0042] All commercial catalysts are listed in the table below and were purchased directly from the manufacturers. All catalysts were stored in a dry environment.
[0043] [Table 1]
[0044] Another catalyst used was 9.76 wt.% ruthenium on carbon (ID: 110005, LOT M17160) supplied by Johnson Matthey. The catalyst contained 0.5% moisture.
[0045] All catalyst support materials: carbon (NORIT SX 1 G), Ti2Al2C (MAX-phase), titania (TiO2), alumina (γ-Al2O3) and zirconia (ZrO2) were obtained from a commercial supplier (Sigma-Aldrich®), dried and stored in a dry environment.
[0046] Catalyst reduction and preparation The catalyst extrudates were crushed in a ceramic mortar and sieved to obtain a mesh size of 105-200 μm. The catalyst particles were transferred to a ceramic crucible and placed in a tube furnace for reduction. In the furnace, the particles were heated with a gas mixture of 7% H in N at 100 ml min -1 The temperature in the furnace was increased by 10°C min until it reached 300-450°C. -1The temperature was increased with a gradient of 0.01%. The temperature was held constant for 180 min. Once the reduction procedure was completed, the temperature was slowly decreased and the 7% H2 / N2 mixture was flushed out with a stream of pure nitrogen.
[0047] Catalyst Screening The authors compared the performance of the synthesized catalysts for the reduction of oxalic acid using QCS reactions (using a Batchington reactor for quick catalyst screening (QCS) developed by Avantium Technologies). In these reactions, tantalum reactors were used instead of stainless steel reactors. These reactors were equipped with Teflon liners inserted into the reactors. Pre-reduced catalyst (see catalyst reduction and preparation section) (50±2.5 mg) was loaded into each reactor, which was then stored for 16 hours. The reactors were closed from the top to prevent air from leaking in and oxidizing the catalyst during the reactor storage step. After 16 hours, stirring beans were added to each reactor. 2 ml of a stock solution of oxalic acid (5 wt.%) in demineralized water was transferred into each reactor with an air-displacement electronic pipette Gilson Pipetman Concept. A septum was placed on each reactor. The reactor lids were installed in a "cross" tightening sequence starting from the center. A torque wrench (5 Nm) was used to create an even distribution of force between the different screws. The reactors were flushed three times with N2 (10 bar) and three times with H2 (10 bar), after which they were placed under approximately 79-bar H2 pressure in a pressurizer. The temperature in the QCS was not actively measured, instead an equilibration procedure was performed prior to the experiment to determine the settings required to maintain 75 °C during the reaction. A stirring speed of 800 rpm was used during the experiment. To stop the reaction, the reactor was removed from the QCS unit and immediately cooled in an ice bath to stop the reaction from continuing. The QCS lid was removed by removing the screws in a "cross" pattern similar to those used during the initial installation sequence. When the lid was removed, gas could be heard escaping from the reactor. The catalyst is removed from the reaction mixture by passing the liquid portion of the mixture through a syringe M-filter, which blocks the solid particles from being passed through.
[0048] Different supports (carbon, TiO2, ZrO2, Al2O3 and Ti3(Al 0.8 Sn 0.2A Ru-Sn catalyst (5 wt.% / 5.9 wt.%, corresponding to a 1:1 molar ratio of Ru:Sn) on SiO2 (C2MAX-phase) was prepared via wet impregnation. Before testing, the catalyst was reduced ex-situ at 350–500 °C in a hydrogen atmosphere.
[0049] QCS experiments were carried out using ruthenium-tin (5 wt.% / 5.9 wt) catalysts on different supports. Conversion (A), selectivity (B) and carbon balance (C) data were obtained by liquid chromatography (LC). Conditions during the reaction: temperature = 75 °C, pressure = 80 bar H2, substrate = oxalic acid (5 wt.%) in demineralized water (2 ml), catalyst / support loading = 50 mg (pre-reduced ex-situ in H2 at 350 °C for 3 h and in-situ at 200 °C for 2 h), stirring speed 800 rpm, time = 2, 4 and 6 h.
[0050] Figure 1 shows the results of QCS experiments on different supports after 2, 4 and 6 hours. The percentage of reaction conversion (A), product selectivity (B) and carbon balance (C) were measured and the amounts of EG, AA, GA, GlyA and OA were determined.
[0051] Single Flow Unit (SFU) Components The flow chemistry experiments were carried out in a trickle bed reactor system. This unit can be divided into different subsections. The gas flows are controlled by two mass flow controllers (MFCs), both nitrogen and hydrogen. The nitrogen MFC has a flow rate of 1000 ml min -1 While the hydrogen MFC was capable of flow rates up to 200 ml min -1 The pressure in the reactor was controlled by a pressure gauge, which applied pressure to a back pressure regulator located after the reactor to regulate the pressure inside the system. The feed section consisted of a Jasco HPLC pump. The flow rates of the liquid feed streams ranged from 0.1 to 5 ml min -1 which was transferred to the reactor separately from the gas stream.
[0052] The reactor used for the experiments was a reactor tube with a length of 30 cm and a diameter of 4.6 mm. The reactor volume of this reactor was 5 ml, of which 1.82 ml was in the isothermal region of the system and thus loaded with catalyst. With a total liquid flow rate in plug-flow mode, the system had a maximum residence time of 18 minutes and a liquid flow rate of 0.1 mL per minute. In trickle-flow operation, the residence time would be somewhat shorter (less liquid was present in the reactor).
[0053] The system had space for eight separate waste sample vials to collect the waste liquid that passed through the reactor and was directed through a selector valve system to the sample vials. The sample vials had two needles inserted, an inlet needle from the selector valve and an outlet needle that released pressure or overflow feed into a "flush" jerrycan. The selector valve itself had 16 channels, eight of which led to the sample vials and eight through a manifold to a "waste" jerrycan.
[0054] The system was equipped with a feed solution heating and stirring system which allowed for heating and stirring of the feed solution to disperse the feed solution more homogenously.
[0055] Reactor Materials Oxalic acid is a good complexing agent and therefore could potentially leach metals from the reactor components or catalyst. To get an idea of leaching, we analyzed the reaction solution after 2 hours of reaction of 25 wt% OA in water at 65°C in a Hastelloy reactor using ICP-OES. We observed significant leaching of chromium, iron and nickel from the catalyst, but no leaching of ruthenium. To study the effect of these metals in solution, we added three times the amount found in the leaching experiments of Cr, Fe and Ni to the starting solution. We noted a 10-15% inhibition of the initial reaction rate. To prevent leaching, we tested non-metallic liners in the Hastelloy reactor and avoided any metal parts coming into contact with the reaction solution. We compared the performance of reactors with and without Teflon and glass liners and found better catalyst stability in those with liners. The authors ran the reaction six times consecutively in the same solvent to amplify the potential effect of leaching. In each of the six reactions, the authors added fresh reactant solution but kept the catalyst in the reactor. The Teflon liner worked best to preserve the catalyst activity as a strong over-reduction to ethylene glycol. Metal ions (Ni, Cr, Mo) at ppm levels from reactor corrosion could be inhibiting catalyst performance and only the Teflon liner provided adequate protection.
[0056] Loading of the reactor The single flow reaction used a 30 cm long stainless steel reactor. Prior to this work, equilibration experiments were performed with this reactor to determine that the isothermal region spanned from 9 to 20 cm from the bottom up. The inner diameter of the reactor was 4.6 mm, which corresponds to a reactor volume of 5 ml (or 1.82 ml in the isothermal region). For each reactor load, the maximum volume (1.82 ml) of catalyst was used to fill the isothermal region of the reactor. The catalyst was reduced ex-situ at 350° C. in a hydrogen atmosphere, loaded into the reactor bed, and pre-reduced in-situ in the flow reactor at 200° C. in a hydrogen atmosphere. The remainder of the reactor was filled with layers of silicon carbide (SiC) and quartz wool.
[0057] Installation of the reactor The stainless steel reactor was equipped with Swagelok fittings. The reactor was attached to the SFU via standard Swagelok installation procedures. Swagelok fittings are the fittings of choice here due to their ability to hold high pressure without leaks.
[0058] analysis Liquid chromatography was performed as follows: Samples were prepared as stock solutions of 0.67 mg stock mL in demineralized water. -1 The concentrations of oxalic acid, glycolic acid, glyoxylic acid, acetic acid, and ethylene glycol were measured using an Agilent Technologies 1260 Infinity II. To confirm the results with a second method, the authors used quantitative IR measurements of the liquid phase in random order. The results were consistent with both methods. EXAMPLES
[0059] The system used for these reactions is a trickle bed reactor system, which allows for unlimited continuous operation and automated collection of 8 samples per experiment without interruption. Jasco HPLC pumps generate the reactant feed flows, while mass flow controllers (MFCs) generate the reference gas (H2 or N2) flow to the reactor. At the top of the reactor, both the feed and gas flows are combined, which causes downstream liquid movement and cocurrent gas movement over the packed catalyst bed.
[0060] Various reaction parameters, such as reaction temperature (50-100 °C), hydrogen pressure (10-60 bar), hydrogen flow (50-200 mL min -1 The effects of the addition / exclusion of the equilibration and pre-reduction steps, liquid / gas ratio, residence time, and the respective temperature were studied. The length and volume of the catalyst bed as well as its loading and the OA concentration (5 wt.% OA in water) were kept constant in all experiments.
[0061] Fresh catalyst was used for each experiment.
[0062] Control Experiment (1) No catalyst - Control experiments were performed to rule out any possible reactions in the trickle-bed reactor with reactant feed flow. These control experiments used a reactor loaded similarly to that described in the "Reactor Loading" section. In the control experiments, the catalyst in the isothermal region of the system was replaced with silicon carbide. Various reactant feed flow rates (from 5 to 0.1 mL min -1 ) was examined.
[0063] Results: Near-zero conversion of oxalic acid to observable reaction products was observed during these reactions. The observed limiting conversions were within the error limits of the analytical method. Liquid chromatography showed only oxalic acid. Finally, in the systems used, oxalic acid was not converted in the absence of any catalyst.
[0064] (2) No Hydrogen - The effect of hydrogen presence was investigated. The reactor was loaded according to the procedure described in the "Reactor Loading" section. In this experiment, a commercial catalyst provided by Johnson Mattey with the following characteristics (9.76 wt.% Ru / C, 0.5 wt.% moisture) was loaded in the isothermal region of the reactor. Instead of hydrogen flow, different nitrogen flows were examined. The reaction conditions during this experiment were similar to the actual experimental conditions described herein that actually obtained glycolic acid, only with nitrogen flow instead of hydrogen.
[0065] Results: Similar to the results of the control experiment without catalyst, no reaction products were obtained from this experiment. The conversions were so marginal that they were within the error limits of the LC analysis, and no conclusions could be drawn regarding any possible conversions that could be derived from these data.
[0066] From control and preliminary experiments it was concluded that the conversion of oxalic acid requires the presence of a catalyst and pressurized hydrogen.
[0067] Note: The by-product ethylene glycol comes from the reduction of glycolic acid, while acetic acid is formed directly from oxalic acid [discussed for example by Santos et al. (Reaction Kinetics, Mechanism and Catalysis (2020) 131:139-151)].
[0068] Example 1 We tested the catalyst Ru1Sn2.3 / C, containing 5 wt% ruthenium and 13.7 wt% tin [a molar ratio of Ru:Sn of 1:2.3 was the most active in our experiments] in a trickle-bed flow reactor. We examined the catalyst performance in the temperature range 50-120 °C. The conversion increased and reached 100% at 70 °C, where only glycolic acid was formed (Figure 2 "Series 1"). The formation of acetic acid (as previously observed above 70 °C with Ru / C catalyst) and the constant over-reduction of glycolic acid to ethylene glycol were avoided by adding Sn to the catalyst. A glycolic acid yield of 100% was obtained in the range 70-100 °C. When we further increased the temperature to 120 °C, the catalyst was deactivated and the conversion dropped to 38%. Subsequently, in the following experiments using catalysts at, for example, 50 and 100° C., it was found that the catalyst became deactivated over the higher temperatures applied (see FIG. 2, “Series 2”). Also, at 100° C., the catalyst became deactivated at longer reaction times.
[0069] Comparative Example 2: Effect of Potassium As this operation is part of the deployment of industrial processes from CO2 to chemicals or polymers, the authors tested the reaction with a real feed stream from an electrochemical acidification reactor, where oxalic acid is produced from potassium oxalate. The only difference with the already established conditions was the lower concentration of oxalic acid at 2.37 wt.% in water. To prove the stability of the method, the authors targeted a reaction time of at least 100 h in a single uninterrupted reaction. Unfortunately, the conversion dropped significantly already after 16.5 h (Figure 3). Read in conjunction with Example 3.
[0070] Example 3 Since the authors had already used the same catalyst used in Comparative Example 2 for over 100 hours without significant deactivation, they suspected the cause was in the actual feed stream and tested it for contaminants. It was found that not all the potassium oxalate was converted to oxalic acid, and 9000 ppm of potassium, a known catalyst poison, was released into the feed stream.
[0071] To allow a side-by-side comparison with Comparative Example 2, the authors prepared a potassium-free solution with the same oxalic acid concentration that resulted in a conversion that stabilized at 88% conversion after 56 hours and remained constant for over 100 hours (Figure 4). The conversion can be increased by temperature, residence time or hydrogen pressure. The selectivity to glycolic acid was 94.5% [no Sn in the catalyst], but the formation of acetic acid still reached 5.5% (4.3 min, 6.7% max).
Claims
1. 1. A method for producing glycolic acid, comprising: The method includes subjecting an aqueous oxalic acid solution to a hydrogenation reaction in the presence of hydrogen and a metal-containing hydrogenation catalyst, A continuous flow process in a fixed bed reactor; The oxalic acid solution does not contain potassium; an aqueous oxalic acid solution and a hydrogen gas stream are fed to a fixed bed reactor, the aqueous oxalic acid solution in the feed stream having an oxalic acid concentration of up to 100% saturation at a feed temperature; the reactor comprises a hydrogenation catalyst bed, the catalyst being a supported metal-containing hydrogenation catalyst with a total metal loading of from 2.0 wt.% to 20.0 wt.%; The hydrogenation reaction is carried out at a temperature selected from the range of 40° C. or more to 85° C. or less at 10 bar H 2 Above 150bar H 2 The process is carried out at a hydrogen pressure selected from the range of 100 to 2000 psi and a residence time of 5 minutes to 1 hour, and produces glycolic acid with a high selectivity of 80% or more at a conversion of 80% to 100% of oxalic acid.
2. 10. The process of claim 1, wherein the reactor is a trickle bed reactor.
3. 3. The process according to claim 1 or 2, wherein the hydrogenation catalyst contains one or more metals selected from group A metals: platinum, nickel, copper, ruthenium, rhodium and iridium, and optionally one other metal selected from group B metals: tin, bismuth, palladium, rhenium, gold and antimony.
4. 4. The process according to claim 1, wherein the hydrogenation catalyst contains ruthenium as a group A metal and preferably one group B metal.
5. 5. The process of claim 4, wherein the hydrogenation catalyst contains ruthenium and tin.
6. 6. The process according to claim 5, wherein the molar ratio of ruthenium to tin in the catalyst is from 10:1 to 1:10, preferably from 5:1 to 1:5, more preferably from 5:2 to 1:
4.
7. 7. The process according to any one of claims 1 to 6, wherein the catalyst is a trimetallic catalyst containing ruthenium, platinum and tin.
8. The hydrogenation catalyst is made of carbon, silicon carbide, MAX-phase (Ti 2 Al 2 C) TiO 2 and ZrO 2 8. The process according to claim 1 , wherein the catalyst is supported on a support selected from the group consisting of carbon and MAX-phase, preferably carbon or MAX-phase, most preferably carbon.
9. 9. The process according to any one of claims 1 to 8, wherein the hydrogenation reaction is carried out in a reactor having a non-metallic or inert liner, preferably selected from Teflon, glass, PVC, titanium and Hastelloy.
Citation Information
Patent Citations
A method of preparing glycolic acid (hoch 2COOH)
WO2017134139A1